Virtualized Network Coding Functions on the Internet - Linquan Zhang; Shangqi Lai; Chuan Wu; Zongpeng Li; Chuanxiong Guo (Proceedings of the International Conference on Distributed Computing Systems, 2017)
Network coding is a fundamental tool that enables higher network capacity and lower complexity in routing algorithms, by encouraging the mixing of information flows in the middle of a network. Implementing network coding in the core Internet is subject to practical concerns, since Internet routers are often overwhelmed by packet forwarding tasks, leaving little processing capacity for coding operations. Inspired by the recent paradigm of network function virtualization, we propose implementing network coding as a new network function, and deploying such coding functions in geo-distributed cloud data centers, to practically enable network coding on the Internet. We target multicast sessions (including unicast flows as special cases), strategically deploy relay nodes (network coding functions) in selected data centers between senders and receivers, and embrace high bandwidth efficiency brought by network coding with dynamic coding function deployment. We design and implement the network coding function on typical virtual machines, featuring efficient packet processing. We propose an efficient algorithm for coding function deployment, scaling in and out, in the presence of system dynamics. Real-world implementation on Amazon EC2 and Linode demonstrates significant throughput improvement and higher robustness of multicast via coding functions as well as efficiency of the dynamic deployment and scaling algorithm.